Modulated Light Dependence of Growth, Flowering, and the Accumulation of Secondary Metabolites in Chilli - Darko, Eva; Hamow, Kamirán A.; Marček, Tihana; Dernovics, Mihály; Ahres, Mohamed; Galiba, Gábor (Frontiers in Plant Science, 2022)
Chili is widely used as a food additive, flavouring and colouring agent and also has great importance in health preservation and therapy due to the abundant presence of many bioactive compounds, such as polyphenols, flavonoids, carotenoids and capsaicinoids. Most of these secondary metabolites are strong antioxidants. In the present study, the effect of light intensity and spectral composition was studied on the growth, flowering and yield of chilli together with the accumulation of secondary metabolites in the fruit. Two light intensities (300 and 500 µmol m-2 s-1) were applied in different spectral compositions. Broad white LED spectrum with and without FR application and with blue LED supplement was compared to blue and red LED lightings in different (80/20 and 95/5%) blue/red ratios. High light intensity increased the harvest index (fruit yield vs. biomass production) and reduced the flowering time of the plants. The amount of secondary metabolites in the fruit varied both by light intensity and spectral compositions: phenolic content and the radical scavenging activity were stimulated, whereas capsaicin accumulation was suppressed by blue light. The red colour of the fruit (provided by carotenoids) was inversely correlated with the absolute amount of blue, green and far-red light. Based on the results a schematic model was created representing light-dependent metabolic changes in chilli. The results indicated that the accumulation of secondary metabolites could be modified by the adjustment of light intensity and spectral composition; however, different types of metabolites required different light environments.